Information Seeking Behaviour in Digital Environment: Exploring the role of search engines in information seeking behavior (Journal of Advances and Scholarly Researches in Allied Education, 2020)
While it is one of the most often discussed topics in user the concept of information seekingis seldom defined. People probably already know the term means what they believe it means, thereforethey do this when they seek information. Seeking knowledge because one has a need to fulfill some aim,as the definition of information-seeking puts it, suggests that the concept of information-seeking is moreclosely related to the idea of need than to the idea of information. In this research, we examine how peopleuse search engines to find information on the modern web.